Virulence and pathogenicity determinants in whole genome sequence of Fusarium udum causing wilt of pigeon pea - Srivastava, Alok K.; Srivastava, Ruchi; Yadav, Jagriti; Singh, Alok K.; Tiwari, Praveen K.; Srivastava, Anchal K.; Sahu, Pramod K.; Singh, Shiv M.; Kashyap, Prem Lal (Frontiers in Microbiology, 2023)
The present study deals with whole genome analysis of Fusarium udum, a wilt causing pathogen of pigeon pea. The de novo assembly identified a total of 16,179 protein-coding genes, of which 11,892 genes (73.50%) were annotated using BlastP and 8,928 genes (55.18%) from KOG annotation. In addition, 5,134 unique InterPro domains were detected in the annotated genes. Apart from this, we also analyzed genome sequence for key pathogenic genes involved in virulence, and identified 1,060 genes (6.55%) as virulence genes as per the PHI-BASE database. The secretome profiling of these virulence genes indicated the presence of 1,439 secretory proteins. Of those, an annotation of 506 predicted secretory proteins through CAZyme database indicated maximum abundance of Glycosyl hydrolase (GH, 45%) family proteins followed by auxiliary activity (AA) family proteins. Interestingly, the presence of effectors for cell wall degradation, pectin degradation, and host cell death was found. The genome comprised approximately 895,132 bp of repetitive elements, which includes 128 long terminal repeats (LTRs), and 4,921 simple sequence repeats (SSRs) of 80,875 bp length. The comparative mining of effector genes among different Fusarium species revealed five common and two specific effectors in F. udum that are related to host cell death. Furthermore, wet lab experiment validated the presence of effector genes like SIX (for Secreted in Xylem). We conclude that deciphering the whole genome of F. udum would be instrumental in understanding evolution, virulence determinants, host-pathogen interaction, possible control strategies, ecological behavior, and many other complexities of the pathogen.